Development and validation of the numerical model of Electron Cyclotron Resonance Ion Sources. (1st June 2022) - Mironov, V.; Bogomolov, S.; Bondarchenko, A.; Efremov, A.; Loginov, V.; Pugachev, D.
Abstract: Processes of the secondary electron emission (SEE) from the walls are included into the Numerical Advanced Model of Electron Cyclotron Resonance Ion Sources (NAM-ECRIS). It is found that SEE strongly influences electron confinement time and ion production. With the modified model, we observe reactions of the source to changes in a gas flow into the source and in an injected microwave power. The source performance with scaling the hexapole magnetic field is investigated. The calculated tendencies are close to the experimental observations.